INTERACTIVE METHODS OF TEACHING ORAL SPEECH - Rustamova Feruzabonu Ilkhomovna; Yomirchiyeva Madina Muhiddinovna (Western European Studies, 2025)
This article explores the effectiveness of interactive methods in teaching oral speech, emphasizing their role in fostering active learner engagement and communication skills. It discusses various interactive approaches, such as project-based learning, cooperative learning, game-based learning, and learning through practice, highlighting their benefits in improving fluency, pronunciation, and confidence in oral communication. The article also provides specific strategies for A2-B1 level learners, including role-playing, guided discussions, linguistic exchanges, and situational activities. Additionally, it addresses techniques for supporting learners who face challenges in oral skills, such as providing structured feedback, encouraging repetition, and using reinforcement activities. By implementing these interactive methods, educators can create a dynamic and engaging learning environment that enhances oral competency effectively
Keywords: Interactive teaching methods; oral speech development; game-based learning